2016
DOI: 10.3897/zookeys.586.6774
|View full text |Cite
|
Sign up to set email alerts
|

New species of Austropurcellia, cryptic short-range endemic mite harvestmen (Arachnida, Opiliones, Cyphophthalmi) from Australia’s Wet Tropics biodiversity hotspot

Abstract: The genus Austropurcellia is a lineage of tiny leaf-litter arachnids that inhabit tropical rainforests throughout the eastern coast of Queensland, Australia. The majority of their diversity is found within the Wet Tropics rainforests of northeast Queensland, an area known for its exceptionally high levels of biodiversity and endemism. Studying the biogeographic history of limited-dispersal invertebrates in the Wet Tropics can provide insight into the role of climatic changes such as rainforest contraction in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Currently, there are 25 described species of Austropurcellia, 21 of which are endemic to the Wet Tropics (Jay et al, 2016). All but six of these twenty-five species have been described in recent years by our research group (Boyer and Reuter, 2012;Popkin-Hall and Boyer, 2014;Boyer et al, 2015;Jay et al, 2016). These discoveries reflect our own collecting efforts as well as examination of museum material, the bulk of which resulted from decades of Wet Tropics leaf litter arthropod surveys by the Queensland Museum.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Currently, there are 25 described species of Austropurcellia, 21 of which are endemic to the Wet Tropics (Jay et al, 2016). All but six of these twenty-five species have been described in recent years by our research group (Boyer and Reuter, 2012;Popkin-Hall and Boyer, 2014;Boyer et al, 2015;Jay et al, 2016). These discoveries reflect our own collecting efforts as well as examination of museum material, the bulk of which resulted from decades of Wet Tropics leaf litter arthropod surveys by the Queensland Museum.…”
Section: Introductionmentioning
confidence: 85%
“…transferred to Austropurcellia by when phylogenetic analysis of molecular data demonstrated that the Queensland species form a monophyletic group. Currently, there are 25 described species of Austropurcellia, 21 of which are endemic to the Wet Tropics (Jay et al, 2016). All but six of these twenty-five species have been described in recent years by our research group (Boyer and Reuter, 2012;Popkin-Hall and Boyer, 2014;Boyer et al, 2015;Jay et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The New Zealand species Aoraki denticulata is known as an example of an old species with extreme population-level variation, without a single haplotype shared between localities as distant as the ones sampled here and with p-distances of up to 22% for the same marker (Boyer et al 2007;Fernández and Giribet 2014). While population-level studies are not yet available, Karripurcellia seems to follow a pattern more similar to that of the eastern Australian Austropurcellia (see Jay et al 2016), whose species are also short-range endemics with distributions rarely spanning more than 50 km and which have been suggested as a model for biogeographic studies of forest corridors and contraction.…”
Section: Discussionmentioning
confidence: 73%
“…Due to their low vagility, restriction to moist habitats, and usually isolated ranges, pettalids follow a typical distribution of short-range endemics (Jay et al 2016), species which inhabit a relatively small area of less than 10,000 km 2 (Harvey 2002), as observed in many SWWA terrestrial arthropods (Rix et al 2015;Harms 2018). The monophyly and validity of Karripurcellia and of one of its species have, however, been questioned by Karaman (2012), who erected the genus Milipurcellia Karaman, 2012 for K. sierwaldae Giribet, 2003, and synonymized K. harveyi Giribet, 2003with K. peckorum Giribet, 2003 Milipurcellia was later synonymized with Karripurcellia in a paper that included sequence data from multiple Karripurcellia specimens from different localities (Giribet et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that some harvestmen species exhibit very short-range distributions, sometimes covering a few kilometers, or in the case of troglobitic species, only a cave or one cave system (Ubick & Ozimec 2005;Jay et al 2016;Cruz-López et al 2019). Troglobitic genera of the family Stygnopsidae, reflecting micro-endemic distributions, are the following: Brujita Cruz-López, in press, Iztlina Cruz-López & Francke, 2017, Mexotroglinus Šilhavý, 1977, Minisge Cruz-López et al, 2019, Tonalteca Cruz-López & Francke, 2017, each restricted to a specific cave system.…”
Section: Discussionmentioning
confidence: 99%